MEDICAL ELECTRONICS - Sodikova Dilnavoz Kambaraliyevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract - this article examines the types of medical electronics, as well as the role of medical technology in modern medicine, and what advantages data obtained using medical devices for monitoring patients' condition can bring.